2008
DOI: 10.4197/islec.21-2.1
|View full text |Cite
|
Sign up to set email alerts
|

Bank Ownership, Characteristics, and Performance:A Comparative Analysis of Domestic and Foreign Islamic Banks in Malaysia

Abstract: Today, the Malaysia Islamic banking system is becoming an effective means of financial intermediation reflected by its extensive distribution networks comprising 152-full-fledgedIslamic banking branches and more than 2,000 Islamic banking counters. The ability of the Islamic banking institutions to arrange and offer products with attractive and innovative features at prices that are competitive with conventional products, has appealed both the Muslim and nonMuslim customers. This has spurred the efforts by oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 26 publications
4
28
0
Order By: Relevance
“…They found that the Islamic banks were more efficient due to Islamic banks' asset-based financing. Sufian and Majid (2006) investigated the comparative efficiency of the foreign and domestic banks of Malaysia during 2001-2005. They found that banks' scale inefficiency dominated pure technical efficiency during the period.…”
Section: Review Of Literaturementioning
confidence: 99%
“…They found that the Islamic banks were more efficient due to Islamic banks' asset-based financing. Sufian and Majid (2006) investigated the comparative efficiency of the foreign and domestic banks of Malaysia during 2001-2005. They found that banks' scale inefficiency dominated pure technical efficiency during the period.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A comparison of 11 financial ratios for the period 1991-2001 found that there was no difference in profitability and liquidity performance between Islamic and conventional banks for that period. Sufian and Majid (2006) investigated the comparative efficiency of the foreign and domestic banks of Malaysia during 2001Malaysia during -2005. They found that banks' scale inefficiency dominated pure technical efficiency during the period.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A.T. Kearney annually ranks emerging market economies based on more than 25 macroeconomic and retail-specific variables through their Global Retail Development Index. In 2005In , 2006In , and 2007 India ranked number one, indicating that the country was the most attractive market for global retailers to enter. This is indicative of an untapped demand.…”
Section: Rising Domestic Demand and Foreign Direct Investment In Retailmentioning
confidence: 99%